Traits-Based Integration of Multi-Species Inoculants Facilitates Shifts of Indigenous Soil Bacterial Community - Wang, Jingjing; Li, Qingqing; Xu, Song; Zhao, Wei; Lei, Yu; Song, Chunhui; Huang, Zhiyong (Frontiers in Microbiology, 2018)
Microbial co-inoculation is considered to be an innovative approach and had been applied worldwide. However, the underlying mechanisms of microbial co-inoculants constructions, especially the trait-based combination of distinctly different microbial species remains poorly understood. In this study, we constructed two microbial co-inoculants with the same three strains with emphasis on the microbial, soil and plant traits. Microbial co-inoculants 1 (M1) were constructed according to soil fertility, microbial activity and cucumber nutrient requirement with a 2:1:2 ratio (Ensifer sp. NYM3, Acinetobacter sp. P16 and Flavobacterium sp. KYM3), while microbial co-inoculants 2 (M2) were constructed according to soil fertility and cucumber nutrient requirement with a 1:10:1 ratio without considering the difference in the nutrient supply capability of microbial species. The results showed that M1 and M2 both obviously increased cucumber yields. The M1 had significant highest pH value, total nitrogen (TN) and Invertase activity (IA). The M2 had significant highest available phosphate (AP), NO3-N, urea activity (UA) and Alkaline phosphatase activity (APA). Gammaproteobacteria, Acidobacteria, Nitrospirae and Armatimonadetes were significantly increased, while Actinobacteria and Firmicutes were significantly decreased by microbial co-inoculations (M1 and M2). The bacterial lineages enriched in M1 were Gammaproteobacteria and TM7. Acidobacteria, Bacteroidetes, and Deltaproteobacteria were enriched in M2. PCoA analysis showed that the bacterial communities were strongly separated by the different microbial inoculation treatments. The functional groups of intracellular_parasites were highest in M1. The functional groups of phototrophy, photoautotrophy, nitrification, fermentation, cyanobacteria, oxygenic_photoautotrophy, chitinolysis and animal_parasites_or_symbionts were highest in M2. Based on correlation analysis, it inferred that the M1 and M2 might promote cucumber yields by mediating bacterial community structure and function about nitrogen fixing and urea-N hydrolysis, respectively. Collectively, these results revealed that microbial co-inoculants had positive effects on cucumber yields. Trait-based integration of different microbial species had significant effects on soil properties and bacterial communities. It indicated that microbial activity should be considered in the construction of microbial co-inoculants. This will expand our knowledge in bacteria interaction, deepen understanding of microbial inoculants in improving plant performance, and will guide microbial fertilizer formulation and application in future.